Transtorno do déficit de atenção e hiperatividade ou indisciplina na escola? - CHAVES, Juliana Silva (2019)
This course completion work aims to analyze the perception that teachers have about discipline or indiscipline of a child with Attention Deficit Hyperactivity Disorder (ADHD), when it does not fit the standards of a regular school in view of the school failure, before his definitive diagnosis. It seeks to understand ADHD, the importance of a diagnosis and the forms of treatment, as well as how it has been approached in the field of Education. The role of the school and the questions regarding the drugs used in this treatment are also the field of study of this research. The main theoretical reference is based on the Manual DSM-5 (2014), Silva (2014), Argollo (2003), Mattos (2003) and Manual DSM-IV (2002). The empirical material was obtained in four schools of the municipality of Barcarena / PA by means of questionnaires for teachers. From the collected data, it can be verified that it is necessary to de-characterize the concept that behaviors outside the patterns can be some type of disorder and which must be medicated. And realizing that this can cause suffering for the child, who presented only certain difficulties in which it was transformed into diseases that needed to be cured, to fit pre-established standards.